Multimedia improves knowledge and choice of contraception among pregnant women - Eka Nur Rahayu; C. Asri Budiningsih; B.M. Wara Kushartati (Intelektual Pustaka Media Utama, 2020)
The quantitative research employed quasi-experimental research with one pretest-posttest group was done to examine the knowledge of pregnant women about family planning and the choosing of contraception. The sample of this study was 41 pregnant women recruited by incidental sampling techniques. Questionnaires for pregnant women provide maternal identity, questions for knowledge about family planning, and the choice of contraception chosen. Data analysis used Wilcoxon test. Multimedia improves the knowledge and choice of contraception among pregnant women.